Water-borne coccidians in Philippine water sheds: A national inceptive study - Masangkay, Frederick R.; Milanez, Giovanni D.; Chua, Natasha Elouise R.; Angulo, Frances Michelle N.; Aquino, Precious Diane M.; Calucin, Daryce Nicole D.; Urtal, Gen-Ghis Ramil O. (Asian Journal of Biological and Life Sciences, 2016)
Water-borne coccidians, one of few emerging pathogens, are not entirely known in developing countries. It has caused illnesses mainly on immunocompromised hosts but can also cause pathology in immunocompetent individuals. Due to the rarity of well-documented occurrences of these pathogens, water samples from a major watershed in Metro Manila, Philippines were investigated. 75 samples, 60 mL each, were filtered to obtain sediments. The sediments were processed and smeared onto glass slides and stained using modified Kinyoun acid-fast technique and microscopically observed for Cryptosporidium and Cyclospora oocysts. The 3-day collection (25 samples per day) yielded positive results: Day 1 produced 19 positive water samples (76%); Day 2 with 17 (68%); and Day 3 with 22 (88%) for Cryptosporidium and Cyclospora oocysts. Overall, oocyst positivity was 58 (77%). Measured physicochemical properties included pH, turbidity, total dissolved solids, fluoride, chloride, nitrate, and conductivity. This study was able to establish an inceptive profile of the presence of Cryptosporidium spp. and Cyclospora spp. oocyst in one of the Major water sheds in the National Capital Region of the Republic of the Philippines.
Keywords: Coccidian; Cryptosporidium; Cyclospora; Watershed